Volunteerism in Context: A Comparison on Habitat for Humanity Canada Programs - Cove, Leslie (My University, 2013)
This thesis applies a Bourdieuian analysis to a qualitative study of volunteerism that focuses on the question of how ‘doing good’ relates to social change overall? - in particular, the ways that social class influences the volunteer experience and the overall culture of volunteerism. I argue that the leading theoretical research models of volunteerism need to recognize the evolving nature of the activity and theorize the influences that are structuring the culture of volunteerism. What emerges is a model of volunteering where motivation is understood as a complex set of factors that are structured by social class identities and volunteering is understood as a form of distinction that can be used to acquire cultural capital. Social class-based ideas, in particular, the values related to the middle class, have become a part of the culture of volunteerism and, in part, create and reproduce the social change/volunteerism paradox. The volunteerism/social change paradox is the idea that volunteerism is often perceived as a social change activity when in many cases it reproduced the status quo. Without a strong activism component to the volunteerism, it is not an inequality challenging activity.
This thesis presents interview and observation data collected with Habitat for Humanity Canada in their two largest programs – the National program (domestic) and the Global Village program (international). By utilizing ideas of class, class distinction and social and cultural capital from Bourdieu’s work, the role of class, the culture of benevolence (or volunteerism) can be explored in a new way. What emerges is a culture of volunteerism that is deeply influenced by middle class values where social change ideas are common but structural change is not – resulting in the volunteer/social change paradox.
Keywords: Volunteerism; Voluntourism; Motivation; Class Identity; Social Networking; Social Change; Community Engagement; Inequality and Stratification; Leisure Studies; Tourism; Community Engagement